Carbon turnover and sucrose metabolism in the culm of transgenic sugarcane producing 1-Kestose - Nicholson, Tarryn Louise (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Genetics. Plant Biotechnology))--University of Stellenbosch, 2007.